Matrine, a potential drug for the treatment of rheumatoid arthritis - Yaping Peng; Xinqiao Lian; Yan Wang; Xin Li (Rheumatology & Autoimmunity, 2024)
Abstract Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease with a multifaceted pathogenesis involving genetic, epigenetic, and environmental factors. It mainly targets the synovium, leading to synovitis and subsequently bone erosion. Novel effective treatments for RA are imperative. Matrine, the main active constituent of Sophora flavescens Ait (known as Kushen in Chinese medicine), has been used to treat fever, dysentery, hematochezia, jaundice, oliguria, vulvar swelling, asthma, eczema, and inflammatory disorders. Matrine exhibits diverse pharmacological effects, including antitumor, anti‐inflammatory, antifibrotic, and antiviral properties. Animal studies have suggested that matrine mitigates inflammation and reduces RA severity by modulating inflammation‐related expression. Its therapeutic mechanism in RA may involve several signaling pathways, including the phosphatidylinositol 3‐kinase/protein kinase B/mammalian target of the rapamycin, nuclear factor‐κB, Janus kinase/signal transducers and activators of transcription, and mitogen‐activated protein kinase pathways, all of which are associated with various biological processes, such as cell proliferation and differentiation, apoptosis, and immune regulation. Moreover, mitochondrial homeostasis disruption and epigenetic modifications, mediated by long noncoding RNAs, play crucial roles in RA pathogenesis. Experimental evidence suggests that matrine exerts therapeutic effects by modulating mitochondrial homeostasis and long noncoding RNAs. We summarize the molecular mechanisms of matrine in RA treatment to provide theoretical support for expanding its clinical applications to the treatment of RA.